2008
DOI: 10.1007/s00540-008-0639-x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma proinflammatory and anti-inflammatory cytokine and catecholamine concentrations as predictors of neurological outcome in acute stroke patients

Abstract: In ischemic stroke, plasma cytokines and catecholamines were not predictors of neurological outcome at 1 month. In hemorrhagic stroke, high levels of IL-6 in the early phase indicated a poor neurological outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 28 publications
2
39
1
Order By: Relevance
“…16 Its role in CNS pathology, however, is less well understood. For example, IL-6 may mediate motor coordination deficits after TBI, 25 appears associated with poor neurological outcome following hemorrhagic stroke, 26 yet may also be involved in regenerative and repair processes. 16 In this study, we show that NE blunted ERK MAPK upregulation in juvenile males, but blocked upregulation in juvenile females after FPI.…”
Section: Discussionmentioning
confidence: 99%
“…16 Its role in CNS pathology, however, is less well understood. For example, IL-6 may mediate motor coordination deficits after TBI, 25 appears associated with poor neurological outcome following hemorrhagic stroke, 26 yet may also be involved in regenerative and repair processes. 16 In this study, we show that NE blunted ERK MAPK upregulation in juvenile males, but blocked upregulation in juvenile females after FPI.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that proinflammatory cytokines, including TNF-α and IL-1β are elevated in serum in the early phase of acute ischemic stroke [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…3). As discussed above, hyperglycemia of diabetes or insulin deficiency-induced generation of ROSs and toxicity to vascular endothelial cells, and/or increased non-enzymatic glycosylation (NEG) of functional proteins (e.g., vascular or extracellular collagen, albumin, hemoglobulin) have been implicated in type-II diabetes complications (e.g., cardiovascular diseases, stroke, retinopathy, nephropathy, neuropathy, hypertension, high serum cholesterol-LDL, or atherosclerosis) [6,18,20,52,82,84,151,190,192,[195][196][197][198][199]. Circulating high glucose levels may induce additional oxidative stress in insulin-independent tissues (e.g., vasculature, retina, RPE, kidney, brain) by modifying or competing with transport, metabolism, and function of important solutes/metabolites or regenerative pathways in ascorbate (vitamin C)-semidehydroascorbate (SDA), pyridoxal phosphate-pyridoxine (vitamin B6), myo-inositol transport and/ or post-modifications of functional proteins, or alterations of NADP ?…”
Section: Metabolic Factors In Agingmentioning
confidence: 99%
“…3) [1,45,50,52,66,74,82,151,[183][184][185][186][187][188][189][190][191][192]. For example, age-associated hormonal alterations in thymic atrophy and associated declines in the genesis of subsets of T cells have been linked to immunoscenescence and chronic diseases [133,[183][184][185][186][187].…”
Section: Hormones and Growth Factorsmentioning
confidence: 99%
See 1 more Smart Citation